Cardiovascular magnetic resonance findings in competitive athletes recovering from COVID-19 infection - Rajpal, S.; Tong, M. S.; Borchers, J.; Zareba, K. M.; Obarski, T. P.; Simonetti, O. P.; Daniels, C. J. (JAMA Cardiology, 2020)
Myocarditis is a significant cause of sudden cardiac death in competitive athletes and can occur with normal ventricular function.1 Recent studies have raised concerns of myocardial inflammation after recovery from coronavirus disease 2019 (COVID-19), even in asymptomatic or mildly symptomatic patients. 2. Our objective was to investigate the use of cardiac magnetic resonance (CMR) imaging in competitive athletes recovered from COVID-19 to detect myocardial inflammation that would identify high-risk athletes for return to competitive play.